2021
DOI: 10.3390/microorganisms9010101
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles and Graphene Oxide Flakes Synergistic Partaking in Cytosolic Bactericidal Augmentation: Role of ROS and NOX2 Activity

Abstract: Gold nanoparticles (GNPs) and graphene oxide flakes (GOFs) exerted significantly (p < 0.0001) supportive roles on the phagocytosis bioactivity of the immune cells of phagocytic nature against the Gram-positive and Gram-negative human pathogenic bacteria Staphylococcus aureus and Escherichia coli. Under experimental conditions, upon bacterial exposure, the combined GNPs and GOFs induced significant clearance of bacteria through phagosome maturation (p < 0.0001) from time-points of 6 to 30 min and producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…This creates a great desire to synthesize nanoparticles with harnessed size and nanometer morphology in an eco-friendly mode [11]. The size and the shape of nanoparticles are permanently related to the unique characteristics, work, and application of nanomaterials [12,13]. Because of its eco-friendliness, low toxicity along with increased stability, small size, and shape distribution, emerging advances in nanoparticle generation using green syntheses are attracting much attention today [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This creates a great desire to synthesize nanoparticles with harnessed size and nanometer morphology in an eco-friendly mode [11]. The size and the shape of nanoparticles are permanently related to the unique characteristics, work, and application of nanomaterials [12,13]. Because of its eco-friendliness, low toxicity along with increased stability, small size, and shape distribution, emerging advances in nanoparticle generation using green syntheses are attracting much attention today [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Monocytes realize defense functions against pathogens via numerous mechanisms including phagocytosis and intracellular killing. Previous works have reported that graphene-based and other nanomaterials can both enhance [ 38 , 39 ] and suppress [ 40 , 41 ] the ability of phagocytic cells to engulf pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…The Student›s t-test was also used to test for significant differences in means. The p value <0.05 was considered to be significant (Al Rugaie et al 2021).…”
Section: Discussionmentioning
confidence: 99%